2000
DOI: 10.1093/molehr/6.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Human cervical ripening, an inflammatory process mediated by cytokines

Abstract: An extensive remodelling process, referred to as cervical ripening, takes place in the cervical tissue during pregnancy and labour. It is recognized as softening and dilation of the cervical canal, and starts as a slow process during pregnancy, becoming rapid close to partum. In this study we focus on cytokines as possible mediators of this final remodelling. mRNA levels for interleukin (IL)-8, IL-6 and granulocyte colony-stimulating factor (G-CSF) were upregulated in the ripe postpartum cervical tissue (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
3
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(181 citation statements)
references
References 48 publications
10
163
3
5
Order By: Relevance
“…Mechanism of cervical ripening had not been clearly defined but it has increased substantially after Danforth et al (1960) had reported it. It has been suggested that pro inflammatory cytokines (Sennstrom et al 2000), connective tissue remodeling regulated by prostaglandins, relaxin and gonadal steroids (Norman et al 1993) may have role on this process. Ding et al (1990) had reported increased in vitro hydrolytic activity in cervical tissue after administration of PGE1 in first trimester pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of cervical ripening had not been clearly defined but it has increased substantially after Danforth et al (1960) had reported it. It has been suggested that pro inflammatory cytokines (Sennstrom et al 2000), connective tissue remodeling regulated by prostaglandins, relaxin and gonadal steroids (Norman et al 1993) may have role on this process. Ding et al (1990) had reported increased in vitro hydrolytic activity in cervical tissue after administration of PGE1 in first trimester pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These pro-inflammatory cytokines have a multitude of effects on the reproductive tissues, including stimulatory effects on myometrial contractility via a number of different mechanisms, discussed below. Cytokines are also involved in tissue remodelling (Sennstrom et al, 2000) and attract more leukocytes in a positive feedback mechanism (Elliott et al, 2000), augmenting the process of parturition. The activity of nuclear factor-kappa B (NF-κB), a transcription factor regulating numerous genes involved in a multitude of cellular processes including inflammation, is also increased in labour ).…”
Section: Labour As An Inflammatory Eventmentioning
confidence: 99%
“…Leukocyte invasion and the increase in protein concentrations of IL-8, IL-6 and granulocyte-CSF (G-CSF) observed in the human cervical connective tissue at term and subsequently in labour are likely to be crucial to the process of cervical remodelling to facilitate opening during parturition (Osman et al, 2003, Sennstrom et al, 2000. Functionally, IL-8 may stimulate the release of degradative enzymes from neutrophils.…”
Section: The Cervixmentioning
confidence: 99%
“…The cellular component is typically below 5-10% per weight [59]. The ECM provides strength and rigidity to resist mechanical loading, and provides a scaffold for cell attachment and migration.…”
Section: Extracellular Matrix Components Of Cervical Tissuementioning
confidence: 99%